Adherence to Therapy after Flexor Tendon Surgery at a Level 1 Trauma Center. (June 2014) - Toker, Serdar; Oak, Nikhil; Williams, Allison; Ipaktchi, Kyros; Ozer, Kagan
Background: Nonadherence to postoperative therapy protocols can adversely affect the outcome after flexor tendon surgery. In this study, we hypothesize that patients with partial or no insurance coverage for their aftercare are less likely to attend postoperative therapy sessions and have a higher incidence of a poorer outcome than those who have full insurance coverage. Methods: We analyzed 159 patients with flexor tendon injuries at a level 1 trauma center. Demographic variables along with the clinical outcome data were collected and cross-tabulated. Associations among descriptive and clinical variables were assessed using Fisher's Exact tests and chi-square analyses. Comparisons for continuous variables were performed using the Kruskal-Wallis Test. Results: Eighteen patients (11.3 %) had an injury in zone 1, followed by 68 (42.8 %) in zone 2, 15 (9.4 %) in zone 3, 9 (5.7 %) in zone 4, 38 (23.9 %) in zone 5, and 11 (6.9 %) in zone 6. Patients completed 8.2 therapy sessions on average. Patients had state assistance program (40.3 %), private insurance (35.2 %), Medicaid/Medicare (11.3 %), worker's compensation (8.8 %) insurance, or paid themselves (13.2 %). Fifty-three (33.3 %) patients had excellent outcomes, 46 (29 %) had good, 40 (25 %) had fair, and 20 (12.5 %) had a poor outcome. Patients responsible to pay for their aftercare were significantly less likely to be adherent to therapy and had poorer outcomes than those with full coverage. Conclusion: Patients responsible for the pay of their postoperative rehabilitation are less likely to participate in therapy and may be at a higher risk of having a poor outcome.